Z rynku prasowego Drugiej Rzeczypospolitej. Odbiorcy i zasięg oddziaływania „Myśli Narodowej” w latach 1921-1939 - Jastrzębski, Przemysław (Acta Universitatis Lodziensis. Folia Librorum, 2010)
In the interwar period the “National Thought” was elite weekly of the national camp about character ideologically – theoretical. The main task of the weekly was adopted by the disclosure of the National Democracy political line and shaping in spirit of members the national camp, as well as wide groups of the public opinion. Circles having with a higher education that is an intelligence and widely understood elites were a recipient of the letter. In contemporary Poland it wasn’t a large group and essentially could count not more than 1.5 m of persons. “National Thought” was for the National Democracy above all the unusually essential tool of attracting the intelligentsia and holding it, as well as other chosen social groups, contacts. Therefore the periodical was characterized by an editorial and technical high level, showing reflections of political, social and cultural most outstanding politicians and national ideologists. The letter was issued in Warsaw and had a nationwide scope although indeed reached the largest municipal centers above all. Effectively the financial problems typical of the Polish press of that period lowered the scope of the letter, relatively low circulation in good years the copy reaching the over 5 thousand and accepted exclusiveness of the periodical. This phenomenon typical of magazines was ideologically – political in the period of interwar Poland. Editors of “National Thought” as an elitist statement, avoid the spectacular marketing activities and therefore the basic form of periodical distribution, essentially limiting the mass range, for which extension in but never was a subscription, and not the street distribution. Subscriptions were made through post offices or direct orders by editors. The newspaper could also be purchased at selected bookstores in the country. The technique adopted was to distribute the newspaper to create the strongest ties to its recipient. Distribution of the letter dealt with the biggest distribution company in Poland –Polish Association of Railway Bookshop “Ruch” from Warsaw leading wholesale distribution of letters in the most remote corners of the country.